Development of Compliant Vibration Isolation Damper and Its Performance Analysis in Turning Operation. (13th September 2022) - Sathyapriya, G.; Natarajan, U.; Sureshkumar, B.; Navaneethakrishnan, G.; Palanisamy, R.; Aboras, Kareem M.; Kotb, Hossam; Kumar Sharma, Naveen; Kitmo,
Abstract : The major setback faced by any of the production industry was maintaining the surface quality and dimensional accuracy of parts manufactured. Higher productivity is expected from industrial point of view, but resulting in poor surface texture. This work aims at addressing this problem by developing a suitable damping system for increased production with high precision products. In conventional method, dampers used is assembled of many parts, whereas the innovation in this paper is that the damper structure is monolithic in nature. Hence, manufacture time and cost of new innovative compliant damper is reduced. The work addressed the problem of damping by the use of compliant mechanism developed through building blocks of planar compliant mechanisms synthesis. Finite element analysis (FEA) was carried out in deciding the final form of the damping system. The proposed design was created by following fused deposition modelling (FDM 3D printing technique) using acrylonitrile butadiene styrene (ABS) material. Based on the results obtained from the experiments, the damping system has an impact on the surface quality of the product. The cutting force produced between the cutting edge and work surface could be improved by providing continuous contact (i.e., higher tool stability). The tool stability could be improved by using the compliant damping design and 3D printing technology for developing the complex designs into real products. The major limitation of the proposed work is the complexity in analysing compliant models with all the boundary conditions prevailing in the real time environment. The major influencing boundary conditions could be applied in neglecting insignificant factors. This work is a novel approach for developing a compliant mechanism-based damper that could restrict the effects of chatter in machining operation. The building blocks-based design was produced using 3D printing of the ABS material. Turning of aluminium was analysed for surface improvement by the tool stability improvement. Results revealed the impact of the ABS compliant damper. On an average, surface roughness of the products was reduced by 27.61%.